Neutrino Spin and Dispersion in Magnetized Medium - P. A. Eminov (Advances in High Energy Physics)
The full energy shift of a massive Dirac neutrino in magnetized electron-positron plasma was investigated using the Matsubara imaginary time and real time formalisms. The neutrino dispersion in the magnetized medium was analyzed as a function of the neutrino spin and mass. It was shown that in a superstrong magnetic field the CP-symmetric plasma contribution to the neutrino energy greatly exceeds the analogous correction in the field-free case. The contribution of plasma to the anomalous magnetic moment of a neutrino was obtained.